The Javanese Panji Story: its transformation and dissemination into the performing arts in Southeast Asia - Bramantyo, Triyono; Hung, Susan (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This paper studies descriptively several versions of Javanese Panji Story with its transformation and dissemination into the performing arts found in Southeast Asia. Accordingly, there are versions varied not only regarding its stories, locations, events, and the style of its narratives but also the flow of the stories. So many other versions have not been described here in this paper just to imagine how this 13th century Javanese literature has turned out to become so many versions. Moreover, the story has spread out not only in Indonesia but also throughout the Southeast Asian archipelago. The writer found that authenticity is not the concern because the original version of the Panji Story was not existed and thus texts can be in so many forms. However, what was overwhelming is that the story had been transformed into so many genres of performing arts in Southeast Asia, such as in Indonesia, Thailand, Cambodia and Myanmar, the former state of Burma. The study found that the performing styles of Panji or Inou in Indonesia, Thailand, Cambodia, and Myanmar shared the same styles as typical classical dance of Royal Palace that performed high standards of performances such as glorifying model of costumes and accompanied by aesthetically qualified Royal Palace Music Ensembles.